Development Dynamics of Remittances in Bangladesh - Munim K. Barai (SAGE Open, 2012)
Remittance inflows in the economy of Bangladesh are getting larger every passing year, matching with the increasing external demand for its manpower. The ensuing development impacts of remittances, as a means of transfer of wealth, on socioeconomic factors are increasingly viewed with importance. Remittances have helped improve the social and economic indicators like nutrition, living condition and housing, education, health care, poverty reduction, social security, and investment activities of the recipient households. The relative weight of remittances has also increased against most of the macroeconomic variables alongside the contribution to GDP. Moreover, Bangladesh has been able to avoid any serious imbalances in BOP’s current account, although it has persistent merchandize trade deficits. Not only that, the export tradable sector has thus far remained unaffected from the Dutch Disease effects of remittances.